PENGARUH PENEMPATAN SUMBER DAYA MANUSIA (SDM), KEMAMPUAN KERJA DAN PENGALAMAN KERJA TERHADAP KINERJA KARYAWAN PT. BPRS BHAKTI SUMEKAR SUMENEP - Sugeng Megawardana; Chamariyah Chamariyah; Subijanto Subijanto (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2020)
This type of research is explanatory research, the research approach uses a quantitative approach, and data analysis uses SPSS. The research sample was 60 employees. The objectives of this study are 1). Analyze and describe HR placement, work ability and employee performance of PT. BPRS Bhakti Sumekar Sumenep. 2). Test and analyze whether the placement of human resources, work ability, simultaneously affect the performance of employees of PT. BPRS Bhakti Sumekar Sumenep. 3). Test and analyze the placement of human resources has a significant influence on the performance of employees of PT. BPRS Bhakti Sumekar Sumenep. 4). Test and analyze work ability has a significant influence on the performance of employees of PT. BPRS Bhakti Sumekar Sumenep. The results showed that: 1). Simultaneously the placement of human resources, work ability has a positive and significant effect on employee performance at BPRS Bhakti Sumekar Sumenep, it is evidenced by the results of the calculated F value of 2,740 with a known significance level of a value of 0.003 (less than 0.05). 2). partially the placement of human resources, work ability has a positive and significant influence on the employee performance of BPRS Bhakti Sumekar Sumenep.